Shot peening impact on fatigue scattered structural elements of vehicles - Sebastian KAMIŃSKI; Tadeusz ŁAGODA (Scientific Journal of Silesian University of Technology. Series Transport)
The theme of this work is to know about the current state of knowledge in the field of materials processing using a distributed circular pellet of shot peening steel surfaces. The paper presents an analysis of the issues and test their own dedicated fatigue life specimens made of steel S355 J2 + N subjected to shot peening, and to compare these results with the strength of the specimens not subjected to this treatment. The results will be presented in the fatigue characteristics S-N double logarithmic system.